New polyoxygenated fatty acid ester and other constituents from Dendrobium nobile Lindl. and their chemotaxonomic significance - Ting Chen; Dan Zhang; Xiujuan Fu; Siwei Chen; Hui Lei; Xiaoxu Bi (Biochemical Systematics and Ecology, 2026)

Impacts of high-altitude aerosol hygroscopicity on cloud microphysics in the North China Plain: A WRF fast-SBM modeling study - Qian Gao; Hui He; Xiang'e Liu; Yan Yang; Rong Yuan; Ping Tian; Kai Bi; Fei Wang; Jiujiang Sheng; Yongqing Wang (Atmospheric Research, 2026)

Robust HPLC-MS/MS quantification of N-acyl homoserine lactones (AHLs) in biomass-associated solid matrices reveals their aqueous–solid distribution in wastewater treatment systems - Xinhao Xu; Xuejun Bi; Hui Zhang; Boyan Xu; Xueqing Shi; Haifeng Zhang; Lihua Cheng; Xiaolin Zhou; Tang Yang; Kibaek Lee; Shujuan Huang; How Yong Ng (Water Research, 2026)

Coffee geographical origin rapid on-site discrimination strategy using an electrochemical fingerprinting platform by optimization of electrolyte concentration and temperature - Chengxiang Yong; Guohua Hui; Zhaoyi Sun; Wenxiong Wu; Yuchen Huang; Huiting Lan; Jianyu Lu; Dianchen Dai; Chengling Xia; Yuqi Xiao; Ying Liao; Zhenjing Su; et al. (Food Chemistry, 2026)

Tailoring polyhydroxybutyrate by molecular weight regulation: Green synthesis, food-grade performance and innovative ketogenic applications - Jin Hui Xie; Jia Ying Xin; Yan Wang; Li Rui Sun; Hai Xin Bi; Jian Xiong Zhang; Chun Gu Xia (Food Research International, 2026)

Circular bioeconomy through a closed-loop anaerobic digestion-pyrolysis biorefinery: techno-economic, environmental and policy perspectives - Hui Zhu; Huimin Zhou; Anthony Lau; Susan Baldwin; Loretta Li; Jack Saddler; Xiaotao Bi (Bioresource Technology, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Bionic nanozyme arrays for selective identifying and discriminating sulfonylurea herbicides via recognition site mimicry - Yuqing Cheng; Tian Tian; Donghui Song; Yu Ma; Zhichun Bi; Xinjian Zhang; Ling Zhang; Yongxin Li; Hui Huang (Journal of Hazardous Materials, 2026)

Beauvericin modulates immune responses in the silkworm, Bombyx mori: insights from cellular and transcriptomic analyses - Jinhua Fan; Yong Bi; Jia Li; Hui Su; Aiying Cheng; Baozhen Li (Journal of Invertebrate Pathology, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

Zircon–monazite geochronology and zircon Hf–O isotopes of Ediacaran–Cambrian paragneiss from the Mashan Complex, Jiamusi Block, NE China: implications for sedimentary–metamorphic–tectonic evolution - Guan-Ying Yu; Hao Yang; Jia-Hao Jing; Zheng Ji; Yan-Long Zhang; Jun-Hui Bi; Wen-Chun Ge (International Geology Review, 2026)

UV–vis spectral based online monitoring and control of ozonation process for tertiary treatment of leather tannery effluent - Hui Zhang; Xiaodong Wang; Tao Ma; Kun Ma; Xiaodong Gou; Ming Zhu; Zakhar Maletskyi; Harsha Ratnaweera; Xuejun Bi (Journal of Water Process Engineering, 2026)

Removing Pb2+ ions from aqueous solution with freshwater cyanobacteria: Combined adsorption and intracellular precipitation - Xiaofei Zhu; Hui Bai; Xiangyang Bi; Haipeng Deng; Neha Mehta; Liyuan Ma; Zhaoyi Dai; Hongmei Wang; Deng Liu (Journal of Hazardous Materials, 2026)

Two distinct patterns for advanced simultaneous nitrogen and phosphorus removal treating low C/N wastewater in a low DO anaerobic/oxic/anoxic-aerobic granular sludge (AOA-AGS) system - Jingwei Ma; Ying Han; Yaning Ji; Hui Sun; Peng Bi; Long Chen; Xinrui Zhang; Xinru Li; Shiquan Ren; Liang Zhu; Qiulai He (Environmental Research, 2026)

Bromine-directed crystallization of phenazine acceptors enables high-efficiency organic solar cells approaching 20% PCE in green solvents - Yingjie Xie; Yaonan Ma; Peng Mao; Tong Wang; Nan Yi; Yue Wang; Xinya Ran; Huijuan Bi; Hui Wang; Dingding Qiu; Yilan Zhai; Caixuan Wang; et al. (Chemical Engineering Journal, 2026)

Exploratory behaviour shapes nutrient versus energy foraging priorities in Java sparrows - Ruiqiu Zhang; Yangkun Bi; Guang Chen; Deji Xue; Zhihui Jin; Donglai Li; Hui Li; Paul Racey; Dongmei Wan; Jiangxia Yin (Behavioural Processes, 2026)

A digital microfluidics-based single-cell ddPCR platform for high-throughput gene copy number analysis applied to single cultured cells - Yicheng Sun; Jiancong Liang; Hui Li; Yechen Fan; Te Peng; Siyi Hu; Yuan Gao; Wenli Zhao; Ling Jiang; Khadija Urooj; Hanbin Ma; Mude Shi; et al. (Analytica Chimica Acta, 2026)

Broadband Vibration Suppression of Spar-Type Offshore Wind Turbines Using a Novel Folded-Beam Nonlinear Energy Sink - Jinyu Li; Hui Liang; Yanliang Bi; Nana Sun; Yan Zhang; Hongyin Geng (Journal of Marine Science and Engineering, 2026)
Spar-type floating offshore wind turbines (FOWTs) operating in deep-sea environments are subjected to coupled wind and wave excitations spanning a wide frequency range, rendering single-frequency passive damping solutions inadequate. A folded-beam nonlinear energy sink (FB-NES) is proposed for broadband vibration suppression of spar-type FOWTs. The device employs pre-buckled elastic beam arms integrated with constrained layer damping patches, and a closed-form analytical relationship between the beam geometric parameters and the nonlinear stiffness coefficients is derived, enabling direct parameter design without iterative calibration. The pre-buckled geometry introduces a negative-stiffness mechanism that substantially lowers the targeted energy transfer (TET) threshold, ensuring device engagement under all normal operational sea states. A 14-degree-of-freedom aero-hydro-elastic model of the NREL 5 MW OC3-Hywind FOWT with the FB-NES is established via the Euler–Lagrange formulation and validated against OpenFAST. Based on the numerical results under operational and extreme parked load cases, the FB-NES achieves substantial broadband vibration reductions that grow monotonically with wave severity, consistently and substantially surpassing both the optimally tuned mass damper (TMD) and a conventional cubic nonlinear energy sink of equal mass. Wavelet analysis confirms that targeted energy transfer, rather than direct viscous damping, is the dominant energy dissipation mechanism. The FB-NES also maintains effective control over a wide frequency detuning range, demonstrating superior robustness compared to the TMD.

Mo/Co-Doped ZIF-67/ZSM-5 catalysts for Atmospheric co-pyrolysis of tobacco stems with urea to enhance pyrrole Yield: Pathway and mechanism analysis driven by hydrodeoxygenation - Xiaoyu Song; Shanjian Liu; Jibin Li; Dongmei Bi; Yu Ni; Hui Wang (Fuel, 2026)

Critical windows and joint effects of prenatal heat and relative humidity exposure on stillbirth: A prospective longitudinal cohort study - Zhan Li; Yuxin Bi; Shuangying Li; Shaofei Su; Lebing Wang; Juan Li; Shuanghua Xie; Enjie Zhang; Minhui Hu; Shaowen Wu; Jianhui Liu; Chenghong Yin; et al. (Environmental Research, 2026)

Salicylic acid-mediated biosynthesis of anti-oomycete diterpenoids in Euphorbia lathyris L. suspension cells - Pirui Li; Xi Sun; Guodong Zhang; Bi Wang; Chenxing Xiao; Mei Tian; Shu Xu; Hui Liu; Xu Feng; Linwei Li; Wanli Zhao; Yu Chen (Plant Cell Reports, 2026)

A coupled strain-damage framework for rock deformation and dynamic damage under cyclic loading based on mesoscale elastoplastic elements - Haohao Zhang; Rui Chen; Yazhou Wang; Huijie Bi; Chaojun Fan; Hui Peng (Computers and Geotechnics, 2026)

Convergent enrichment of core functional guilds involved in Fe-N metabolism in anammox and activated sludge: Insights into genome-resolved metagenomics - Hui Sun; Ying Han; Shiquan Ren; Xinrui Zhang; Xinru Li; Peng Bi; Long Chen; Liang Zhu; Guangchao Yang; Jingwei Ma; Qiulai He (Bioresource Technology, 2026)

Java sparrows can modulate vocalizations in response to different light wavelengths - Deji Xue; Jinhong Chen; Yangkun Bi; Ruiqiu Zhang; Guang Chen; Donglai Li; Hui Li; Dongmei Wan; Paul Racey; Jiangxia Yin (Behavioural Processes, 2026)

Isolation and identification of a centromeric tandemly repeated DNA sequence in Saccharina japonica - Yi-Yan Cai; Cheng Zhang; Si-Qi Chen; Zhi Li; Zhi-Gang Zhou; Yan-Hui Bi (Algal Research, 2026)

Metabolic Engineering of Selenocysteine Biosynthesis and Insertion Pathway in Lactococcus Lactis - Jing-Jing Peng; Yao Qin; Shi-Yang Yue; Ping Shi; Ling-Yu Wang; Chen-Xing Liu; Yu-Hui Fang; Xiao-Dong Pei; Fu-Tian Yu; Xin-Bi Huang; Xiao-Ling Liu; Cheng-Hua Wang (Biological Trace Element Research, 2026)

A new genetic programming approach to dynamic multi-point dynamic aggregation problem - Ying Bi; Xishui Xue; Ya-Hui Jia; Caitong Yue; Kai Zhang (Swarm and Evolutionary Computation, 2026)

The insecticidal activity and mechanism of the Cinnamomi ramulus (Lauraceae) essential oil against Tribolium confusum Jaquelin Du Val, 1868 (Coleoptera: Tenebrionidae): insights from transcriptomic and metabolomic profiles - Qianqian Lian; Jianji Zhao; Yiqing Li; Hui Tang; Yanping He; Qiuling Tang; Wei Zhang; Jie Bi (Journal of Stored Products Research, 2026)

Selective separation of rare earth from acetatesolution containing aluminum by nonequilibrium extraction - Linlin Chang; Jian Li; Dongyue Xie; Xudong Liu; Yaobin Lai; Jiayi Zan; Chenjiahui Wang; Yangyang Xie; Xuxia Zhang; Hui Zhang; Tao Qi; Rongde Li; et al. (Journal of Environmental Management, 2026)

Human activity intensifies land subsidence in the Yellow River Delta - Hui Xu; De Wang; Rongrong Ning; Xiaoyong Li; Xinpeng Tian; Xiaoli Bi; Zixiang Zhou; Yongwei Zhang (Estuarine, Coastal and Shelf Science, 2026)

Strategy for doubling the yield of phenolics in hydrothermal liquefaction of Arundo donax: mechanistic study on weak alkaline catalyst suppressing hydrochar formation and enriching phenolics in aqueous and biocrude phases - Lei-ming Bi; De-lin Fu; Xian-shuai Fu; Li-hui Zhang; Feng Duan (Biomass and Bioenergy, 2026)

Probabilistic space-time prisms in road networks with travel time uncertainties - Hui-Ping Chen; Zhi-Chun Li; Bi Yu Chen (Journal of Transport Geography, 2026)

Drivers of biogenic secondary organic aerosols in Eastern China: Evidence from machine learning and high-resolution measurements - Kun Zhang; Meng Xiu; Xiaohui Bi; Yanan Yi; Rui Li; Biao Zhou; Ruixin Pan; Hui Chen; Jian Zhen Yu; Li Li (Journal of Hazardous Materials, 2026)

Effect of S, N co-doped carbon-based supports on low-temperature NH3-SCR: Resistance to SO2, H2O and denitrification mechanism - Shuangshuang Yan; Dongmei Bi; Shiyan Sun; Hui Wang; Xiang Zhu; Long Wang; Shanjian Liu (Journal of Environmental Chemical Engineering, 2026)

Enhanced selectivity for the removal of Al3+ from the simulated rare earth leachate via a 3D electrochemical hydrolysis process - Chenjiahui Wang; Jian Li; Dongyue Xie; Xudong Liu; Jiayi Zan; Linlin Chang; Yaobin Lai; Yangyang Xie; Xuxia Zhang; Hui Zhang; Tao Qi; Rongde Li; et al. (Desalination, 2026)

Brachymonas moutaii sp. nov., a floc-forming bacterium isolated from a distillery wastewater treatment plant - Yaqi Liu; Hui Wang; Ansi Jiang; Junmei Wu; Bi Chen; Yong Zhang; Siliang Yuan; Yan Huang; Haiyan Zeng; Xin Wang; Dian Jiao; Wei Li; et al. (Antonie van Leeuwenhoek, 2026)

Niche differentiation drives microbial community assembly in an anaerobic/oxic/anoxic-aerobic granular sludge (AOA-AGS) system: Insights into Anammox self-enrichment - Jingwei Ma; Hui Sun; Yaning Ji; Qiulai He; Long Chen; Ying Han; Peng Bi; Liang Zhu (Water Research, 2026)

Numerical modeling of CO2 storage and gas recovery enhancement in low-permeability carbonate reservoirs via acid-fractured horizontal wells - Jiangtao Hu; Shenglai Yang; Lufei Bi; Xinyuan Gao; Hui Deng; Ermeng Zhao (Fuel, 2026)

Scopolamine exerted antidepressant-like behavioral effects via restoring the synaptic plasticity in CRS-treated mice - Peng-Wei Bi; Si-Rui Sun; Jia-Ning Zhao; Hui-Ying Zhang; Ze Lv; Yong-Yu Yin; Yun-Feng Li (Metabolic Brain Disease, 2025)

Characterizing the marine recreational fishery of Hong Kong using data compiled from a social media platform - Bi Wei Low; Hilton H.C. Fu; Harris C.Y. Poon; Alex H.B. Liu; Heok Hui Tan; Kelvin K.P. Lim; Anthony Lau (Regional Studies in Marine Science, 2025)

Physics-constrained interpolation synergizes with machine learning for diethyl phthalate removal mechanism in water under sparse data - Dongmei Bi; Hui Wang; Shuangshuang Yan; Chengxizi Zhang; Jiawen Zhang; Shanjian Liu; Weiming Yi (Journal of Environmental Chemical Engineering, 2025)

Enhanced ofloxacin degradation by three-dimensional electrochemical activation of peroxymonosulfate using nano ZVC doped reed straw biochar particle electrode - Wenwen Zhang; Jiahui Bi; Yufei Hui; Guangyang Wang; Ran Ma; Hongjie Wang (Journal of Environmental Chemical Engineering, 2025)

Colorimetric/fluorescent/photothermal multi-model sensor array based on the nanozyme for differentiating tea polyphenols and white tea vintages - Xiaoyu Yang; Jie Li; Zhichun Bi; Yu Gu; Yongxin Li; Hui Huang (Food Research International, 2025)

Potential and applications of stable oxygen isotope chronologies for tree-ring dating in South Korea - En-Bi Choi; Jun-Hui Park; Masaki Sano; Takeshi Nakatsuka; Jeong-Wook Seo (Dendrochronologia, 2025)

Establishing ring width and cell chronologies for predicting future growth of Thuja koraiensis under climate change - Jun-Hui Park; En-Bi Choi; Ho-Young Lee; Jeong-Wook Seo (Dendrochronologia, 2025)

In-situ constructed Schottky heterointerface in flexible TiO2@TiC-SiC nanofiber mats for enhancing electromagnetic wave absorption and thermomechanical stability - Hui Zhu; Xiaolong Weng; Ming Liao; Jin Zheng; Mei Bi (Chemical Engineering Journal, 2025)

Valorizing wood processing waste into an all-natural bulk structural material - Kun Liu; Yuan Wang; Dayong Ren; Wujie Dong; Hui Bi; Wei Zhao; Fuqiang Huang (Chemical Engineering Journal, 2025)

Balancing water efficiency and crop productivity: rhizosphere microbiome shifts in drought-resistant rice - Junguo Bi; Jiayi Li; Saeed ur Rahman; Yuchong Long; Nan Hui; Martin Romantschuk; Junqiang Zheng; Xianxian Zhang; Danping Hou; Jinsong Tan; Qingyu Bi; Hui Xia; et al. (World Journal of Microbiology and Biotechnology, 2025)

Constitutive androstane receptor activation modulates YAP expression and activity through ubiquitination and sumoylation - Fengting Liang; Shuaishuai Zhang; Wenhong Zhou; Guofang Bi; Xiao Yang; Peng Wang; Shicheng Fan; Shuang Hu; Chenghua Wu; Xiaowen Jiang; Dan Li; Hui Ouyang; et al. (Toxicology Letters, 2025)

Biosynthetic rule-guided theoretical chemical space mapping strategy for enhanced analysis of plant metabolomes: application to the geographical profiling of goji berry - Wan-Yang Sun; Zhi-Hui Luo; Jie-Qi Cai; Qian Guo; Guo-Tao Chen; Guo-Dong Chen; Dan Hu; Hai-Guang Gong; Xue Li; Wei Bi; Ying Wang; Kwok-Fai So; et al. (Science Bulletin, 2025)

Solar radiation on complex underlying surfaces in Xinjiang: A typical arid and semi-arid region in the northwestern China - Chengming Zhang; Xin Liu; Shuyi Chen; Jianrong Bi; Yonghang Chen; Qing He; Ting He; Yunhong Xu; Hui Li (Journal of Atmospheric and Solar-Terrestrial Physics, 2025)

Integration of partial nitrification, endogenous denitrification and anaerobic ammonia oxidation in low dissolved oxygen anaerobic/oxic/anoxic-aerobic granular sludge reactor treating low carbon to nitrogen ratios wastewater - Jingwei Ma; Long Chen; Yaning Ji; Hui Sun; Ying Han; Liang Zhu; Peng Bi; Qiulai He (Bioresource Technology, 2025)

Development of electrospun nanofiber membranes based on ZIF-8 MOF loaded tea polyphenols with pH-responsive release capabilities for food preservation - Yu Ma; Xinjian Zhang; Junjie Li; Zhichun Bi; Jie Li; Zhenglong Ma; Hui Huang; Yongxin Li (Innovative Food Science & Emerging Technologies, 2025)

The facile discriminative detection of four synthetic antioxidants in edible oil by a multi-signal sensor array based on the Bop-Cu nanozyme combining machine learning - Xinyue Zhang; Linxue Zhen; Zhichun Bi; Peize Jin; Yu Ma; Yongxin Li; Hui Huang (Food Research International, 2025)

Integrating HS-SPME-GCMS with chemometrics for identifying adulterated flaxseed oils and tracing origins of additives - Yan-Jin Wen; Long-He Wang; Meng Zhai; Hui Ma; Hua-Peng Cui; Lu Han; Guo-Bi Chai; Yi Lv; Qing-Xia Zheng; Yong-Jie Yu; Yuan-bin She (Food Control, 2025)

The threat of microplastics to human kidney health: Mechanisms of nephrotoxicity and future research directions - Ru-Yu Tan; Qin-Ying She; Yun-Ci Ma; Ming-Hong Liu; Li-Juan Li; Li-Li Huang; Yi-Wen Zhong; Hui-Xin Bi (Environmental Research, 2025)

A three-channel nanozyme sensor array combined with machine learning algorithm for the differentiation and detection of aminoglycoside antibiotics - Linxue Zhen; Jie Li; Zhichun Bi; Xinyue Zhang; Peize Jin; Hui Huang; Yongxin Li (Chemical Engineering Journal, 2025)

Flexible supercapacitors with biomass-derived nitrogen-functionalized few-layer carbon for wireless energy harvesting and management - Dayong Ren; Peihao Yang; Jiaqi Wang; Zhengxiang Song; Pengyue Wu; Zhanqiang Liu; Tianquan Lin; Hui Bi; Fuqiang Huang (Chemical Engineering Journal, 2025)

Microbially induced phosphate precipitation disentangles sludge retention time trade-off enabling efficient phosphorus removal with minimal sludge discharge in aerobic granular sludge - Peng Bi; Xiaohui Yan; Yueying Song; Hebin Miao; Hui Sun; Ying Han; Long Chen; Kangxin Yan; Mingyang Li; Fan Xiong; Jingwei Ma; Qiulai He (Chemical Engineering Journal, 2025)

Advanced low C/N wastewater treatment in an AOA-AGS sequencing batch reactor via aerobically stimulating simultaneous nitrification and denitrification - Jiyi Chen; Long Chen; Yang Liu; Jingwei Ma; Weihong Wu; Xiang Wang; Yaning Ji; Yuhong Wen; Peng Bi; Hui Sun; Ying Han; Xinrui Zhang; et al. (Journal of Water Process Engineering, 2025)

Optimizing woody oil biodiesel production in yellowhorn via phenotypic marker development: a study of trait–index associations and germplasm screening - Wei Zhang; Linkun Li; Puxia Wu; Hui Yang; Huihui Xu; Quanxin Bi; Changchun Shi; Libing Wang (Journal of Plant Physiology, 2025)

Carbon dots improved the electrochemical reduction performance of Co/AC particle electrodes for humic acid removal: The dominant role of H∗ - Wenwen Zhang; Yufei Hui; Jiahui Bi; Hongjie Wang; Wenyan Liang (Journal of Environmental Management, 2025)

Discrimination of tea varieties and bud sprouting phenology using UAV-based RGB and multispectral images - Litao Sun; Jiazhi Shen; Yilin Mao; Xiaojiang Li; Kai Fan; Wenjun Qian; Yu Wang; Caihong Bi; Hui Wang; Yang Xu; Jingbiao Xu; Zhaotang Ding (International Journal of Remote Sensing, 2025)

Electro-cultivation of hydrogen-oxidizing bacteria to promote ammonia resource recovery and microbial protein synthesis in microbial electrolysis cell - Jingwei Ma; Long Chen; Qiulai He; Hui Sun; Ying Han; Liang Zhu; Peng Bi (Chemical Engineering Journal, 2025)

Schiff base crosslinking based dialdehyde-chitosan/gelatin/tea polyphenol electrospun nanofibrous membranes with excellent antibacterial and antioxidant activity for food packaging - Yu Ma; Ru Tian; Yudong Song; Mengxiao Liu; Jie Li; Zhichun Bi; Hui Huang; Yongxin Li (Food Packaging and Shelf Life, 2025)

Independent and joint effects of volatile organic compounds on pulmonary function in U.S. adults from NHANES: the mediating role of platelet-to-lymphocyte ratio - Yan-Fei Wei; Hao-Wen Chen; Kuan Liu; Shi-Ao Wang; Wei-Dong Fan; Zhan-Hui Shao; Bi-Fei Cao; Yong-Qi Liang; Zheng-Yun Xu; Kai-Yue Liao; Zi-Xuan Zhao; Lu-Rong Yang; et al. (Environmental Pollution, 2025)

Mechanically robust and thermally stable mineralized cellulose bulk structural materials via capillarity-assisted densification - Kun Liu; Yuan Wang; Dayong Ren; Wujie Dong; Hui Bi; Wei Zhao; Fuqiang Huang (Chemical Engineering Journal, 2025)

Co-pyrolysis of polyurethane and biomass: Piperidine derivative production and nitrogen mechanism modulation by flame retardants - Yu Ni; Dongmei Bi; Shuangshuang Yan; Hui Wang; Chunwang Dong; Shanjian Liu (Chemical Engineering Journal, 2025)

Three-channel Sensor Array based on Switchable Nanozymatic Reactions of a Novel Trimetallic Nanozyme for Anti-interference Identification of Tea Adulteration - Jie Li; Linxue Zhen; Zhichun Bi; Yu Ma; Hui Huang; Yongxin Li (Chemical Engineering Journal, 2025)

Role of benzothiadiazole in regulating reactive oxygen species and inhibiting cap opening in Agaricus bisporus during storage - Ruirui Yang; Yanan Wei; Hui Peng; Ting Wang; Jianmin Yun; Yan Yin; Yang Bi (Postharvest Biology and Technology, 2025)

Sensing H2O2 for defense in plants - Yan Bi; Leeza Tariq; Hui Wang; Fengming Song (Molecular Plant, 2025)

Implications of the different submerged extent of typical sandbars to local DOM and SDOM during the pre-flood season in the middle reaches of Yangtze River - Haoyang Shi; Hui Guo; Wenjun Yang; Chengcheng Bao; Xinxin Zhu; Sheng Bi; Yu Hu; Ting Li (Journal of Environmental Management, 2025)

High-throughput screening of acetals/ketals in edible essences via GC-Orbitrap-MS and their formation rates at room temperature - Xiaoyu Wang; Qiong Guo; Lining Pan; Cong Nie; Yiming Bi; Yaqiong Qin; Fuwei Xie; Fangqi Du; Yuhan Peng; Bing Wang; Ruihong Liu; Hui Wang; et al. (Food Chemistry, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

A new feature selection algorithm combining genetic algorithm, exponential decay function, and machine learning to realize hyperspectral estimation of winter wheat leaf area index - Chenbo Yang; Juan Bai; Hui Sun; Rutian Bi; Lifang Song; Amjad Muhammad; Chao Wang; Yu Zhao; Wude Yang; Lujie Xiao; Meijun Zhang; Xiaoyan Song; et al. (Computers and Electronics in Agriculture, 2025)

Functional potential of compound probiotics fermented soybean meal partially replacing fish meal in spotted seabass (Lateolabrax maculatus): Insights through growth, immunity, antioxidant capacity and intestinal health - Bi-Yun Zhang; Ze-Hui Yuan; Hai-Xia Yu; Hong-Ling Yang; Guo-He Cai; Chun-Xiao Zhang; Jie Su; Yun-Zhang Sun (Aquaculture, 2025)

Seismic activity characteristics of the Tongkuang Shan fault (Southeastern Tian Shan, China) revealed by high-resolution topographic data - Hui Qiu; Haiyun Bi; Wenjun Zheng; Jiangyuan Zeng; Bingxu Liu; Shiqi Wei (Journal of Asian Earth Sciences, 2025)

Design and evaluation methods for CFST members with high-performance materials subjected to axial impact - Xiaoqiang Yang; Liguo Zhu; Kaiming Bi; Hui Zhao; Yong Zhu; Zhichao Lai (Engineering Structures, 2025)

Overcoming the conventional thermodynamic limit of water electrolysis to boost renewable energy storage - Hui Sun; Wen-Tao Bi; Qian He; Li Zhu; Yu-Qing Dong; Fang Li; Zhen-Guo Guo; Jun Ding; Jian-Bo He (Chemical Engineering Journal, 2025)

Regulatory Roles and Therapeutic Potential of miR-122-5p in Hypoxic-Ischemic Brain Injury: Comprehensive Review - Abdulaziz S. Bamahel; Xun Sun; Wei Wu; Chenxi Mu; Jia Liu; Sheng Bi; Hui Xu (Cell Biochemistry and Biophysics, 2025)

MMP13 as an effective target of an active trifluoromethyl quinazoline compound against osteosarcoma - Chang-hua Zhou; Ting Zhang; Jia Yu; Gang Yu; Sha Cheng; Hui Wu; Bi-xue Xu; Heng Luo; Xiao-bin Tian (Toxicology and Applied Pharmacology, 2025)

An evolutionary optimization-learning hybrid algorithm for energy resource management - Rui Qi; Ya-Hui Jia; Wei-Neng Chen; Ying Bi; Yi Mei (Swarm and Evolutionary Computation, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Nitrogen-doped porous hydrochar for enhanced chromium(VI) and bisphenol A scavenging: Synergistic effect of chemical activation and hydrothermal doping - Jianhua Qu; Fansong Meng; Fuxuan Bi; Zhao Jiang; Mengning Wang; Qi Hu; Yupeng Zhang; Hui Yu; Ying Zhang (Environmental Research, 2025)

Inorganic-rich solid electrolyte interphase and oriented (002) crystal plane extension for reversible zinc metal anode - Biyao Du; Jingzhu Chen; Yang Xu; Zhuoran Lv; Peng Ying; Wujie Dong; Luke Yan; Hui Bi; Fuqiang Huang (Chemical Engineering Journal, 2025)

Design of an In Vitro Model for Epithelial-to-Mesenchymal Transition in Gastric Cancer - Yuanhui Zhang; Ling Bi; Quanyao Li; Liqiu Yao; Xiao Wang; Hui Liu; Jun Shi (Biochemical Genetics, 2025)
Epithelial-to-mesenchymal transition (EMT) is a developmental program that plays a vital role in gastric cancer, including aspects of tumor progression, the metastatic process, and resistance to treatment. Here, we have designed an in vitro model that mimics the features of EMT as observed in gastric cancer. The results showed that both migration and invasion were enhanced in gastric cancer cells with Brachyury overexpression. Additionally, the expression of IL-8 increased, while IL-8RA and IL-8RB levels significantly decreased in the in vitro model. Overall, the in vitro model offers an opportunity to study these phenomena relevant to EMT as they may occur in vivo in gastric cancer, as well as potential drug interactions that could interfere with these processes.

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

One-step microwave method synthesis of N, S-codoped carbon with the frustrated Lewis pairs for Cr (VI) removal - Liwen Wang; Yixin Sha; Changjun Bi; Daoqing Lin; Yuxue Liu; Lichun Dai; Xiaozhi Wang; Hui Lin; Jawad Ahmad Jrar; Jianhua Hou (Journal of Water Process Engineering, 2025)

A novel sensor array with ability to respectively identify phenol and ketone for the precise discrimination of origins of raw Pu-erh and its counterfeiting - Zhichun Bi; Linxue Zhen; Jie Li; Peize Jin; Yu Gu; Yu Ma; Donghui Song; Xiaoyu Yang; Yongxin Li; Hui Huang (Food Research International, 2025)

Unveiling the structure–activity correlation in iron phosphorus trichalcogenide to realize enhanced potassium ion storage - Xiao-Hui Wu; Bi-Cui Chen; Zhi-Qiang Gu; Xian Lu; Hou-Yang Zhong; Pei-Weng Huang; Jie Zhang; Xue-You Tan; Yi Zhao (Chemical Engineering Journal, 2025)

Comprehensive comparison of water quality risk and microbial ecology between new and old cast iron pipe distribution systems - Youyi Chen; Huishan Zhou; Hui Gao; Ziliang Su; Xinjun Li; Peng Qi; Tong Li; Chun Hu; Zesong Li; Zhihao Bi; Xueci Xing; Jingxin Yang; et al. (Journal of Environmental Sciences, 2024)

Eco-friendly sustainable fluorescent coal-based carbon dots as a highly selective probe for Cu2+detection - Yanxia Bi; Baolin Xing; Huihui Zeng; Bing Xu; Jianbo Jia; Yuanfeng Wu; Guangxu Huang; Chuanxiang Zhang; Hui Guo; Yijun Cao (Fuel, 2024)

Lattice energy transfer from homo-crystalline substitution for enhanced piezo-photocatalytic CO2 conversion - Chuanzhou Bi; Hangmin Xu; Ganghua Zhou; Hao Song; Jian Xu; Qijun Li; Bin Wang; Penghui Ding; Lvzhou Li; Paul K. Chu; Hui Xu; Xingwang Zhu; et al. (Chemical Engineering Journal, 2024)

MsDUF3700 overexpression enhances aluminum tolerance in alfalfa shoots - Jiamin Cao; Tingting Wang; Dian Yu; Junyi He; Wenwu Qian; Bingxia Tang; Xiaojing Bi; Hui Wang; Yunwei Zhang (Plant Cell Reports, 2024)

A novel mutation in hERG gene associated with azithromycin-induced acquired long QT syndrome - Yun-Jiu Cheng; Yang Wu; Hui-Qiang Wei; Yi-Jian Liao; Li-Ping Qu; Yue-Han Pan; Li-Juan Liu; Wen-Tao Bi (Molecular Biology Reports, 2024)

Mechanisms of intermittent theta-burst stimulation attenuating nerve injury after ischemic reperfusion in rats through endoplasmic reticulum stress and ferroptosis - Xin-Ya Shen; Xing-Yu Zhang; Ping-Ping Han; Yi-Ning Zhao; Guo-Hui Xu; Xia Bi (Molecular Biology Reports, 2024)
Background Repetitive transcranial magnetic stimulation (rTMS) exerts neuroprotective effects early in cerebral ischemia/reperfusion (I/R) injury. Intermittent theta-brust stimulation (iTBS), a more time-efficient modality of rTMS, improves the efficiency without at least decreasing the efficacy of the therapy. iTBS elevates cortical excitability, and in recent years it has become increasingly common to apply iTBS to patients in the early post-IS period. However, little is known about the neuroprotective mechanisms of iTBS. Endoplasmic reticulum stress (ERS), and ferroptosis have been shown to be involved in the development of I/R injury. We aimed to investigate the potential regulatory mechanisms by which iTBS attenuates neurological injury after I/R in rats. Methods Rats were randomly divided into three groups: sham-operated group, MCAO/R group, and MCAO/R + iTBS group, and were stimulated with iTBS 36 h after undergoing middle cerebral artery occlusion (MCAO) or sham-operated. The expression of ERS, ferroptosis, and apoptosis-related markers was subsequently detected by western blot assays. We also investigated the mechanism by which iTBS attenuates nerve injury after ischemic reperfusion in rats by using the modified Neurological Severity Score (mNSS) and the balance beam test to measure nerve function. Results iTBS performed early in I/R injury attenuated the levels of ERS, ferroptosis, and apoptosis, and improved neurological function, including mNSS and balance beam experiments. It is suggested that this mode of stimulation reduces the cost per treatment by several times without compromising the efficacy of the treatment and could be a practical and less costly intervention.

Sex-Specific Associations Between Organophosphate Esters Metabolites and Metabolic Dysfunction-Associated Fatty Liver Disease in Chinese Adults - Qing Liu; Gaojie Fan; Jianing Bi; Xiya Qin; Qing Fang; Mingyang Wu; Surong Mei; Zhengce Wan; Yongman Lv; Youjie Wang; Lulu Song; Hui Chen (Exposure and Health, 2024)

Alteromonas arenosi sp. nov., a novel bioflocculant-producing bacterium, isolated from intertidal sand - Bi Luo; Jing-Yun Su; Ya-Fei Zhang; Yong-Hui Xiao; Yun-Lin Peng; Mei-Ling Sun; Yi Li (Antonie van Leeuwenhoek, 2024)

Stress-relieved hollow porous carbon nanoring structures anchored with ZnCo2O4 nanoparticles towards super stable lithium storage - Lishen Ai; Zongbin Zhao; Yong Li; Honghui Bi; Faquan Zhang; Hui Li; Xuzhen Wang; Jieshan Qiu (Chemical Engineering Journal, 2024)

Prioritising challenges and actions for freshwater conservation in a tropical biodiversity hotspot - Alexandra Zieritz; Christopher Gibbins; Yixiong Cai; Farah Diba; Lydia X. Gan; Manuel Lopes-Lima; Jose Christopher E. Mendoza; John Morse; Ting Hui Ng; Elysia X.P. Toh; John Pfeiffer; Bi Wei Low; et al. (Biological Conservation, 2024)

Dominance and rarity in tree communities across the globe: Patterns, predictors and threats - Iris Hordijk; Lalasia Bialic‐Murphy; Thomas Lauber; Devin Routh; Lourens Poorter; Malin C. Rivers; Hans ter Steege; Jingjing Liang; Peter B. Reich; Sergio de‐Miguel; Gert‐Jan Nabuurs; Javier G. P. Gamarra; et al. (Global Ecology and Biogeography, 2024)
Aim Ecological and anthropogenic factors shift the abundances of dominant and rare tree species within local forest communities, thus affecting species composition and ecosystem functioning. To inform forest and conservation management it is important to understand the drivers of dominance and rarity in local tree communities. We answer the following research questions: (1) What are the patterns of dominance and rarity in tree communities? (2) Which ecological and anthropogenic factors predict these patterns? And (3) what is the extinction risk of locally dominant and rare tree species? Location Global. Time period 1990–2017. Major taxa studied Trees. Methods We used 1.2 million forest plots and quantified local tree dominance as the relative plot basal area of the single most dominant species and local rarity as the percentage of species that contribute together to the least 10% of plot basal area. We mapped global community dominance and rarity using machine learning models and evaluated the ecological and anthropogenic predictors with linear models. Extinction risk, for example threatened status, of geographically widespread dominant and rare species was evaluated. Results Community dominance and rarity show contrasting latitudinal trends, with boreal forests having high levels of dominance and tropical forests having high levels of rarity. Increasing annual precipitation reduces community dominance, probably because precipitation is related to an increase in tree density and richness. Additionally, stand age is positively related to community dominance, due to stem diameter increase of the most dominant species. Surprisingly, we find that locally dominant and rare species, which are geographically widespread in our data, have an equally high rate of elevated extinction due to declining populations through large‐scale land degradation. Main conclusions By linking patterns and predictors of community dominance and rarity to extinction risk, our results suggest that also widespread species should be considered in large‐scale management and conservation practices.

In vivo RNAi screening identifies multiple deubiquitinases required for the maintenance of intestinal homeostasis in Drosophila - Boyu Zhao; Jing Luo; Hui Wang; Yuanxin Li; Dong Li; Xiaolin Bi (Insect Biochemistry and Molecular Biology, 2024)

Interaction mechanisms among Cellulose, Hemicellulose, and lignin in Nitrogen-Rich pyrolysis under K and Ca Presence: Intermediate evolution and product formation - Dongmei Bi; Zhisen He; Fupeng Huang; Guanshuai Zhang; Hui Wang; Shanjian Liu (Chemical Engineering Journal, 2024)

Supercapacitor-isolated water electrolysis for renewable energy storage - Qian He; Hui Sun; Wen-Tao Bi; Xin-Yuan Wang; Bing Li; Fang Li; Zhen-Guo Guo; Jun Ding; Jian-Bo He (Chemical Engineering Journal, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Repeated Ketamine Anesthesia during the Neonatal Period Impairs Hippocampal Neurogenesis and Long-Term Neurocognitive Function by Inhibiting Mfn2-Mediated Mitochondrial Fusion in Neural Stem Cells - He Huang; Ning Wang; Jia-Tao Lin; Yong-Kang Qiu; Wei-Feng Wu; Qiang Liu; Chen Chen; Hai-Bi Wang; Yan-Ping Liu; Wei Dong; Jie Wan; Hui Zheng; et al. (Molecular Neurobiology, 2024)

Microplastic and Heavy Metals Distributions in Urban Rivers Sediments, China - Dandan Song; Yujun Shang; Xiuli Wang; Yuwei Zhuang; Hui Guo; Shuping Bi; Jianjun Hu (Journal of Ocean University of China, 2024)

Modified Metal–Organic Framework (MOF-818) inspired by natural enzymes for intelligent detection of total antioxidants and bisphenol A in infant beverages - Jie Li; Luwei Wang; Yu Ma; Zhichun Bi; Yongxin Li; Hui Huang (Analytica Chimica Acta, 2024)

Enhanced silicate weathering accelerates forest carbon sequestration by stimulating the soil mineral carbon pump - Tongtong Xu; Zuoqiang Yuan; Sara Vicca; Daniel S. Goll; Guochen Li; Luxiang Lin; Hui Chen; Boyuan Bi; Qiong Chen; Chenlu Li; Xing Wang; Chao Wang; et al. (Global Change Biology, 2024)
Enhanced silicate rock weathering (ERW) is an emerging strategy for carbon dioxide removal (CDR) from the atmosphere to mitigate anthropogenic climate change. ERW aims at promoting soil inorganic carbon sequestration by accelerating geochemical weathering processes. Theoretically, ERW may also impact soil organic carbon (SOC), the largest carbon pool in terrestrial ecosystems, but experimental evidence for this is largely lacking. Here, we conducted a 2‐year field experiment in tropical rubber plantations in the southeast of China to evaluate the effects of wollastonite powder additions (0, 0.25, and 0.5 kg m −2 ) on both soil organic and inorganic carbon at 0–10 cm depth. We found that ERW significantly increased the concentration of SOC and HCO 3 − , but the increases in SOC were four and eight times higher than that of HCO 3 − with low‐ and high‐level wollastonite applications. ERW had positive effects on the accrual of organic carbon in mineral‐associated organic matter (MAOM) and macroaggregate fractions, but not on particulate organic matter. Path analysis suggested that ERW increased MAOM mainly by increasing the release of Ca, Si, and Fe, and to a lesser extent by stimulating root growth and microbial‐derived carbon inputs. Our study indicates that ERW with wollastonite can promote SOC sequestration in stable MOAM in surface soils through both the soil mineral carbon pump and microbial carbon pump. These effects may have been larger than the inorganic CDR during our experiment. We argue it is essential to account for the responses of SOC in the assessments of CDR by ERW.

Effects of arsenic on gut microbiota and its bioaccumulation and biotransformation in freshwater invertebrate - Xiaoyang Bi; Yan Wang; Aiting Qiu; Shengze Wu; Wenhui Zhan; Hui Liu; Huashou Li; Rongliang Qiu; Guikui Chen (Journal of Hazardous Materials, 2024)

Occurrence, distribution, and ecological risk assessment of pharmaceuticals and personal care products in the surface water of Lipu River, China - Yanan Zhang; Guibin Huang; Qin Zhang; Xiaoqian Bi; Hang Chu; Zixuan Liu; Jun Luo; Shaoyuan Bai; Shengpeng Mo; Hui Wang; Mingming Fu (Environmental Research, 2024)

Tetrabromobisphenol-A/S and their derivatives in surface particulates from workshop floors of three representative e-waste recycling sites in China - Hui Yang; Xiao-Jun Luo; Jia-Zhuo He; Yan-Hong Zeng; Bi-Xian Mai; Li-Zhong Wang; Xiang Bi (Environmental Research, 2024)

Lightweight, mechanically robust and scalable cellulose-based foam enabled by organic-inorganic network and air drying - Hao Sun; Hui Zhu; Penghui Zhu; Pu Yang; Zhengyang Yu; Dingyuan Zheng; Xia Sun; Andrea Vo; Xiaotao Bi; Min Xu; Feng Jiang (Chemical Engineering Journal, 2024)

Determining the optimal thin layer height for single-station ionospheric modeling and its influence on the estimation of DCB - Hui Xi; Hu Jiang; Jiachun An; Na Cheng; Tianyang Bai; Jingxue Bi (GPS Solutions, 2024)

Revealing nitrogenous VX metabolites and the whole-molecule VX metabolism in the urine of guinea pigs - Pei-Yu Jiang; Ling Yuan; Dong-Xin Liu; Hui-Lan Yu; Xiao-Jing Bi; Qiao Lv; Yang Yang; Chang-Cai Liu (Journal of Hazardous Materials, 2024)

Alleviating effect of Astragalus polysaccharide on salinity-alkali stress-induced intestinal injury in hybrid crucian carp - Xin-yu Lei; Jia Sun; Cheng-cheng Bi; Xin Wang; Xue Cao; Hui-qing Wang; Yue-hong Li (Aquaculture International, 2024)

Effectiveness of a novel compound microbial agent for water quality and the gut microbiota of Micropterus salmoides - Qian Li; Li-Hui Sun; Bi-Cheng Yang; Jian-Hu Jiang; Jian-Ming Chen; Gang Zheng; Ling-Mei Gao; Jun Peng; Jian-Lin Guo (Frontiers in Marine Science, 2024)
The cultivation of largemouth bass ( Micropterus salmoides ), a species of significant economic value in aquaculture, has experienced notable growth recently. However, the deterioration of water quality seriously affects the metabolic responses of M. salmoides . While compound microbial agent (CMA) is widely utilized for ecological rehabilitation and water filtration, its application in M. salmoides has not been reported. Here, based on physio-biochemical tests and 16S rRNA sequencing, we investigated the effects of CMA (yeast, Bacillus subtilis , and lactic acid bacteria) on the water quality within the recirculating aquaculture system, along with physiological indices and gut microbiota of M. salmoides . Compared to the control and single microbial agent (yeast), CMA treatment improved the water quality by improving the dissolved oxygen and delaying the increase of pH, total nitrogen, total phosphorus, ammonia nitrogen, and nitrite. The 16s rRNA gene sequencing revealed that the water treated with CMA exhibited elevated levels of chao1, Shannon, Pd, and a larger population of dominant bacterial. Besides, higher values of ACE, chao1, Shannon, and OTU level, and lower Simpson index were found in CMA treated M. salmoides samples, suggesting that CMA treatment enhanced the species richness and diversity of gut microbiota of M. salmoides . Furthermore, CMA treatment hindered the generation and proliferation of harmful bacteria, such as the Mycoplasma mobile 163K species and the Erysipelotrichaceae family, which was associated with enhanced antioxidant enzymatic activity and decreased MDA level in both the serum and liver. These findings shed light on the essential roles of CMA in M. salmoides culturing and introduce an innovative approach to enhance the aquatic environment.

N6-methyladenosine analysis unveils key mechanisms underlying long-term salt stress tolerance in switchgrass (Panicum virgatum) - Huayue Liu; Mengzhuo Lin; Hui Wang; Xue Li; Die Zhou; Xiaojing Bi; Yunwei Zhang (Plant Science, 2024)

Investigation on the joint travel behavior in bike sharing systems during the COVID-19 pandemic: Insights from New York City - Hui Bi; Hui Gao; Aoyong Li; Zhirui Ye (Journal of Transport Geography, 2024)

Biomass-derived polycarboxylate–aluminum–zirconium complex tanning system: A sustainable and practical approach for chrome-free eco-leather manufacturing - Yue Yu; Hui Wang; Yunhang Zeng; Jianfei Zhou; Yi Zhang; Bi Shi; Ya-nan Wang (Journal of Cleaner Production, 2024)

Enrichment process, structural prediction, isolation, in vitro cytotoxic and anti-inflammatory effects of triterpenoid saponins in Camellia japonica L. leaves water extract through UPLC-Q-TOF based mass spectrometry similarity networking - Hui Liu; Lisha Bi; Qirun Chen; Xiaozhi He; Huan Yan; Wei Ni; Wenjuan Wu; Li He; Haiyang Liu (Food Chemistry, 2024)

A new comprehensive quantitative index for the assessment of essential amino acid quality in beef using Vis-NIR hyperspectral imaging combined with LSTM - Fujia Dong; Yongzhao Bi; Jie Hao; Sijia Liu; Weiguo Yi; Wenjie Yu; Yu Lv; Jiarui Cui; Hui Li; Jinhua Xian; Sichun Chen; Songlei Wang (Food Chemistry, 2024)

Isolation of Rhizobacteria from Crocus Sativus L. Rhizosphere and Their Effects on Host-Growth Promotion - Jing-Chao Xu; Xing-Guang Xie; Xue-Wen Bi; Jia-Hao Zhang; Zi-Hui Zhao; Khalid Rahman; Bo Zhu; Lu-Ping Qin; Ting Han (Journal of Plant Growth Regulation, 2024)

Enhanced rock weathering increased soil phosphorus availability and altered root phosphorus‐acquisition strategies - Boyuan Bi; Guochen Li; Daniel S. Goll; Luxiang Lin; Hui Chen; Tongtong Xu; Qiong Chen; Chenlu Li; Xing Wang; Zhanqing Hao; Yunting Fang; Zuoqiang Yuan; et al. (Global Change Biology, 2024)
Enhanced rock weathering (ERW) has been proposed as a measure to enhance the carbon (C)‐sequestration potential and fertility of soils. The effects of this practice on the soil phosphorus (P) pools and the general mechanisms affecting microbial P cycling, as well as plant P uptake are not well understood. Here, the impact of ERW on soil P availability and microbial P cycling functional groups and root P‐acquisition traits were explored through a 2‐year wollastonite field addition experiment in a tropical rubber plantation. The results show that ERW significantly increased soil microbial carbon‐use efficiency and total P concentrations and indirectly increased soil P availability by enhancing organic P mobilization and mineralization of rhizosheath carboxylates and phosphatase, respectively. Also, ERW stimulated the activities of P‐solubilizing ( gcd , ppa and ppx ) and mineralizing enzymes ( phoADN and phnAPHLFXIM ), thus contributing to the inorganic P solubilization and organic P mineralization. Accompanying the increase in soil P availability, the P‐acquisition strategy of the rubber fine roots changed from do‐it‐yourself acquisition by roots to dependence on mycorrhizal collaboration and the release of root exudates. In addition, the direct effects of ERW on root P‐acquisition traits (such as root diameter, specific root length, and mycorrhizal colonization rate) may also be related to changes in the pattern of belowground carbon investments in plants. Our study provides a new insight that ERW increases carbon‐sequestration potential and P availability in tropical forests and profoundly affects belowground plant resource‐use strategies.

A proteomic study on gastric impairment in rats caused by microcystin-LR - Shang-Chun Li; Li-Hong Gu; Yan-Fang Wang; Li-Mei Wang; Liang Chen; John P. Giesy; Xun Tuo; Wen-Li Xu; Qian-Hui Wu; Yi-Qing Liu; Ming-Huo Wu; Yang-Yang Diao; et al. (Science of The Total Environment, 2024)

Provenance and sedimentary environment of REY-rich sediments from the Wharton Basin, Indian Ocean - Jia Li; Mu Huang; Miao Yu; Dongjie Bi; Xuefa Shi; Fengdeng Shi; Chengfei Hou; Zhaojun Song; Fangyu Shen; Aimei Zhu; Hui Zhang; Yonghua Wu; et al. (Journal of Asian Earth Sciences, 2024)

Enhancement of ester biosynthesis in blueberry wines through co-fermentation via cell–cell contact between Torulaspora delbrueckii and Saccharomyces cerevisiae - Yu Wang; Yu Fu; Qi Zhang; Yue Zhu; Qin Yang; Chen Bian; Lu-Lu Zhao; Qi Chen; Hai-Jun Bi; Xiao-Hui Yang; Xue-Ling Gao (Food Research International, 2024)

Preparation of smart magnetic fluids and application in sewage treatment: Copper adsorption, kinetic and isotherm study - Deli Xiao; Hui Jiang; Yunlin Zhou; Alhassan Imran; Hongyan Zhao; Yanping Bi (Journal of Environmental Management, 2024)

Mobility, bacterial hosts, and risks of antibiotic resistome in submicron bioaerosols from a full-scale wastewater treatment plant - Tang Yang; Xuyi Wang; Lu Jiang; Xiaoliang Hui; Xuejun Bi; Xiang Zheng; Bo Jiang; Xiaodong Wang (Journal of Environmental Management, 2024)

NH3 plasma synthesis of amino modified NiCo layered double hydroxide nanoflowers for carbon dioxide photoreduction - Yanhua Song; Zeen Zheng; Jiao Luo; Hangmin Xu; Kang Zhong; Anqi Zhou; Hao Song; Chuanzhou Bi; Jinman Yang; Md Shouquat Hossain; Hui Xu; Xingwang Zhu (Journal of Environmental Chemical Engineering, 2024)

Evaluation of energy-environmental-economic benefits of CNG taxi policy using multi-task deep-learning-based microscopic models and big trajectory data - Bi Yu Chen; Qi Liu; Weishu Gong; Jia Tao; Hui-Ping Chen; Fu-Rong Shi (Travel Behaviour and Society, 2024)

An updated review of the genus Rhododendron since 2010: Traditional uses, phytochemistry, and pharmacology - Xing-Jian Liu; Hai-Guo Su; Xing-Rong Peng; Hui-Chang Bi; Ming-Hua Qiu (Phytochemistry, 2024)

A colorimetric sensor array based on peroxidase activity nanozyme for the highly efficient differential sensing of tea polyphenols and Tieguanyin adulteration - Xiaoyu Yang; Zhichun Bi; Chenghui Yin; Shuyi Zhang; Donghui Song; Hui Huang; Yongxin Li (Food Chemistry, 2024)

New paleoseismic events reveal decamillenial recurrence time for large earthquakes (M ≥ 7) along the Yuguang Graben Fault in North China - Hui Peng; Wenjun Zheng; Shaopeng Dong; Qiyun Lei; Haiyun Bi; Xulong Wang; Dongli Zhang; Xinnan Li; Zhikang Gong; Jinhua Du (Tectonophysics, 2023)

Assessment of oxalates and phytic acid contents in Asian green leafy vegetables: Dietary recommendations - Hui Wen Lee; Xinyan Bi; Christiani Jeyakumar Henry (Food and Humanity, 2023)

Expression of a periplasmic β-carbonic anhydrase (CA) gene is positively correlated with HCO3- utilization by the gametophytes of Saccharina japonica (Phaeophyceae, Ochrophyta) - Hui-Min Hao; Yan-Hui Bi; Ning-Ning Wei; Pei-Chong Lin; Shou-Hua Mei; Zhi-Gang Zhou (Journal of Applied Phycology, 2023)

Aroma enhancement of blueberry wine by postharvest partial dehydration of blueberries - Yu Wang; Qi Zhang; Meng-Yao Cui; Yu Fu; Xiao-Han Wang; Qin Yang; Yue Zhu; Xiao-Hui Yang; Hai-Jun Bi; Xue-Ling Gao (Food Chemistry, 2023)

Bimetallic alloy Fe Co1-PS3 with boosted lithium reaction kinetics for lithium-ion batteries - Hou-Yang Zhong; Yun Chai; Xian Lu; Pei-Wen Huang; Bi-Cui Chen; Ke-Zhao Du; Xiao-Hui Wu (Chemical Engineering Journal, 2023)

A multifunctional surgical suture with electroactivity assisted by oligochitosan/gelatin-tannic acid for promoting skin wound healing and controlling scar proliferation - Hui Han; Liqin Tang; Yan Li; Yong Li; Ming Bi; Jun Wang; Fujun Wang; Lu Wang; Jifu Mao (Carbohydrate Polymers, 2023)

Emerging applications of biochar: A review on techno-environmental-economic aspects - Hui Zhu; Qing An; Amirah Syafika Mohd Nasir; Alexandre Babin; Sofia Lucero Saucedo; Amzy Vallenas; Loretta Li; Susan Anne Baldwin; Anthony Lau; Xiaotao Bi (Bioresource Technology, 2023)

Immunogenicity and safety of an Escherichia coli-produced human papillomavirus (types 6/11/16/18/31/33/45/52/58) L1 virus-like-particle vaccine: a phase 2 double-blind, randomized, controlled trial - Yue-Mei Hu; Zhao-Feng Bi; Ya Zheng; Li Zhang; Feng-Zhu Zheng; Kai Chu; Ya-Fei Li; Qi Chen; Jia-Li Quan; Xiao-Wen Hu; Xing-Cheng Huang; Kong-Xin Zhu; et al. (Science Bulletin, 2023)

Chalcogen-modified copper-nitrogen co-doped carbon as a stable and efficient antimicrobial cathode catalyst for microbial fuel cells - Bi-Lin Lai; Hai-Xia Liao; Shu-Qi Zhou; Hui-Xu Wei; Ai-Yi Li; Nan Li; Zhao-Qing Liu (Journal of Environmental Chemical Engineering, 2023)

Manipulating chaotropic anion enables lacked H-bond aqueous electrolyte for lithium-ion hybrid capacitor - Dewei Xiao; Shen Bi; Langyuan Wu; Min Xue; Lijie Han; Zhenming Xu; Hui Dou; Xiaogang Zhang (Chemical Engineering Journal, 2023)

p-Nrf2/HO-1 Pathway Involved in Methamphetamine-induced Executive Dysfunction through Endoplasmic Reticulum Stress and Apoptosis in the Dorsal Striatum - Tao Wei; Jun-Da Li; Yu-Jing Wang; Wei Zhao; Fan Duan; Yan Wang; Ling-Ling Xia; Zhao-Bin Jiang; Xun Song; Yu-Qiong Zhu; Wen-Yi Shao; Ze Wang; et al. (Neurotoxicity Research, 2023)

Antibiotic resistome associated with inhalable bioaerosols from wastewater to atmosphere: Mobility, bacterial hosts, source contributions and resistome risk - Tang Yang; Xuyi Wang; Xiaoliang Hui; Lu Jiang; Xuejun Bi; How Yong Ng; Xiang Zheng; Shujuan Huang; Bo Jiang; Xiaolin Zhou (Water Research, 2023)

Domesticating aquatic plants in hydroponic systems to demonstrate and advance phytoremediation of the artificial sweetener acesulfame - Xiaoyan Ma; Sinong Huang; Yuhong Jin; Hui Liao; Shaoning Chen; Hong Wang; Weijie Zhang; Yifei Wu; Weiwei Bi; Xueyan Li; Andrea M. Dietrich (Science of The Total Environment, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Sodium acetate trihydrate/melamine foam composite PCM encapsulated by CuS/rGO modified epoxy resin and endowed with light-to-heat conversion properties - Henghua Zhang; Qianbin Dong; Yaping Tang; Jialing Wu; Wenjian Bi; Yue Gao; Jiabang Wang; Hui Yang (Chemical Engineering Journal, 2023)

Heterologous expression of MiMLDP, a major lipid droplet protein of the microalga Myrmecia incisa, in Saccharomyces cerevisiae promotes more triacylglycerol storage principally by enlarging lipid droplet size - Jian-Min Hu; Zheng Sun; Qi-Hui Xu; Xiao-Peng Fang; Yan-Hui Bi; Zhi-Gang Zhou (Algal Research, 2023)

Cosmetics for the non-elite 2000 years ago: affordable raw materials and a complex production process - Meng Wu; Zhongming Tang; Nan Bi; Qinghua Yang; Hui Fang; Quanyu Wang (Archaeological and Anthropological Sciences, 2023)

Contribution of theanine to the temperature-induced changes in aroma profile of Wuyi rock tea - Jing Wang; Haijun Bi; Mengru Li; Hui Wang; Manman Xue; Jieyao Yu; Chi-Tang Ho; Liang Zhang; Qinglin Zhuo; Jiadao Jiang; Xiaochun Wan; Xiaoting Zhai (Food Research International, 2023)

The impacts of spatio-temporal variation of natural and agricultural influences on the environmental water quality in a fluvial-lacustrine watershed in China - Yu Feng; Bing-Hui Zheng; Hai-Feng Jia; Bing-Bing Song; Yang Liu; Jun-Ping Bi (Environmental Science and Pollution Research, 2023)

Precipitation and in-situ surface modification of calcium carbonate in synthetic seawater: Polymorph control, crystallization kinetics, and hydrophobic vaterite preparation - Mengmeng Sun; Hui Jin; Xiaofu Guo; Shizhao Wang; Jingtao Bi; Zhiyong Ji; Yingying Zhao (Journal of Environmental Chemical Engineering, 2023)

Shewanella subflava sp. nov., a novel multi-resistant bacterium, isolated from the estuary of the Fenhe River into the Yellow River - Bi Luo; Jing-Yun Su; Ya-Nan Wang; Li Guan; Kai-Shi Dong; Hui-Jing Niu; Shao-Fei Shen; Yi Li (Antonie van Leeuwenhoek, 2023)

Investigating price fluctuations in copper futures: Based on EEMD and Markov-switching VAR model - Hui Su; Na Zhou; Qiaosheng Wu; Zhiwei Bi; Yuli Wang (Resources Policy, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Bicycle safety outside the crosswalks: Investigating cyclists' risky street-crossing behavior and its relationship with built environment - Hui Bi; Aoyong Li; He Zhu; Zhirui Ye (Journal of Transport Geography, 2023)

Influences of water level fluctuation on water exchange and nutrient distribution in a bay: Evidence from the Xiangxi Bay, Three Gorges Reservoir - Wei He; Siyuan Feng; Yonghong Bi; Aili Jiang; Yuan Li; Wei Huang; Jian Zhang; Hui Xu; Chunsheng Liu (Environmental Research, 2023)

Cyclodextrin-functionalized magnetic alginate microspheres for synchronous removal of lead and bisphenol a from contaminated soil - Jianhua Qu; Zhuoran Li; Zhihuan Wu; Fuxuan Bi; Shuqi Wei; Min Dong; Qi Hu; Yifan Wang; Hui Yu; Ying Zhang (Chemical Engineering Journal, 2023)

Large-scale moisture transport and local-scale convection patterns associated with warm-sector heavy rainfall over South China - Guicai Ning; Ming Luo; Xueyan Bi; Zhizhao Liu; Hui Zhang; Meng Huang; Xiaogang Huang; Yuanjian Yang; Sijia Wu (Atmospheric Research, 2023)

Aircraft observation of fast initiation of mixed phase precipitation in convective cloud over the Tibetan Plateau - Delong Zhao; Minghuai Wang; Daniel Rosenfeld; Baojun Chen; Dantong Liu; Xuexu Wu; Kang Hu; Shuo Ding; Yannian Zhu; Yi Zeng; Yi Qu; Yang Gao; et al. (Atmospheric Research, 2023)

Enzyme-trigger ratiometric fluorescent nanoplatform for diagnosis and imaging of oral diseases - Ming Bi; Yong Li; Pinyi Ma; Yijun Li; Xiaowen Yuan; Hui Han (Analytica Chimica Acta, 2023)

Karyotype analysis of the brown seaweed Saccharina (or Laminaria) japonica - Yan-Hui Bi; Zhi Li; Zhi-Gang Zhou (Algal Research, 2023)

Simultaneous determination of dissolved organic nitrogen, nitrite, nitrate and ammonia using size exclusion chromatography coupled with nitrogen detector - Wen-Xiang Ji; Ye-Chao Tian; Min-Hui Cai; Bi-Cun Jiang; Shi Cheng; Yan Li; Qing Zhou; Bo-Qiang Li; Bai-Yang Chen; Xing Zheng; Wen-Tao Li; Ai-Min Li (Journal of Environmental Sciences, 2023)

Two-dimensional reduced graphene oxide/polypyrrloe-based coating enable superior corrosion protection and photothermal-induced in-situ internal environmental regulation - Ruoqi Chen; Huanrong Zhang; Xinlei Ma; Yuqiao Chai; Haibo Bi; Hui Ma; Nan Zhu; Junhui Ji; Mianqi Xue (Chemical Engineering Journal, 2023)

Multiscale ecosystem service synergies/trade-offs and their driving mechanisms in the Han River Basin, China: implications for watershed management - Bowen Zhang; Liang Zheng; Ying Wang; Na Li; Jiangfeng Li; Hui Yang; Yuzhe Bi (Environmental Science and Pollution Research, 2023)

Acute polyethylene microplastic (PE-MPs) exposure activates the intestinal mucosal immune network pathway in adult zebrafish (Danio rerio) - Yin Yuan; Marisol S. Sepúlveda; Baoliang Bi; Yadong Huang; Lingfu Kong; Hui Yan; Yu Gao (Chemosphere, 2023)

ZIF-8-derived Cu, N co-doped carbon as a bifunctional cathode catalyst for enhanced performance of microbial fuel cell - Bi-Lin Lai; Hui-Xu Wei; Zi-Nuo Luo; Tong Zheng; Yi-Hui Lin; Zhao-Qing Liu; Nan Li (Science of The Total Environment, 2023)

Cr(VI) adsorption and reduction by magnetite-humic acid adsorption complexes under mildly acidic conditions: Synergistic/antagonistic mechanism and multi-step reaction model - Jingjie Chang; Jia Zhang; Hui Wang; Yunfei Bai; Yu Liu; Yanze Bi; Huanzhen Zhang; Honghan Chen; Samuel Barnie; Haijiao Xie (Chemical Engineering Journal, 2023)

Alterations in gut microbiota and metabolites associated with altitude-induced cardiac hypertrophy in rats during hypobaric hypoxia challenge - Zhiyuan Pan; Yichen Hu; Zongyu Huang; Ni Han; Yan Li; Xiaomei Zhuang; Jiye Yin; Hui Peng; Quansheng Gao; Wenpeng Zhang; Yong Huang; Yujun Cui; et al. (Science China Life Sciences, 2022)

Development and Validation of a Diagnostic Nomogram to Predict the Anthracycline-Induced Early Cardiotoxicity in Children with Hematological Tumors - Zhi-yuan Liu; Yun-gong Wang; Xiao-bi Huang; Xiao-hui Qi; Cui-ping Qian; Sheng Zhao (Cardiovascular Toxicology, 2022)
This study aimed to establish and validate an effective nomogram to predict the risk of cardiotoxicity in children after each anthracycline treatment. According to the inclusion and exclusion criteria, the eligible children were randomly divided into the training cohort (75%) and the validation cohort (25%). Least absolute shrinkage and selection operator (LASSO) regression was used to select the predictors and a nomogram was developed. Then, concordance index ( C -index), the area under the curve (AUC), Hosmer–Lemeshow (H–L) test, and decision curve analysis (DCA) were employed to evaluate the performance and clinical utility of nomogram. Internal validation was processed to inspect the stability of the model. A total of 796 eligible children were included in this study and divided into a training set ( n = 597) and a validation set ( n = 199). LASSO regression analysis revealed that cumulative anthracycline dose, ejection fractions, NT-proBNP, and diastolic dysfunction were effective predictors of cardiotoxicity. The nomogram was established based on these variables. The C -index and the AUC of the predicting nomogram were 0.818 in the training cohort and 0.773 in the validation cohort, suggesting that the nomogram had good discrimination. The calibration curve of the nomogram presented no significant deviation from the reference line, and the P -value of the H–L test was 0.283, implying a preferable degree of calibration. The threshold of DCA also reflects that the nomogram is clinically useful. A nomogram was developed to predict anthracycline chemotherapy-induced cardiotoxicity in children with hematological tumors. The nomogram has a good prediction effect and can provide a reference for clinicians’ diagnosis and treatment.

Acetylsalicylic acid (ASA) suppressed Fusarium rot development and neosolaniol (NEO) accumulation by activating phenylpropane metabolism in muskmelon fruit - Lan Li; Qili Liu; Huali Xue; Yang Bi; Hussain Raza; Rui Zhang; Jimdjio Kouasseu Carelle; Hui Peng; Haitao Long; Dov Prusky (European Journal of Plant Pathology, 2022)

Hippocampal SIRT1-Mediated Synaptic Plasticity and Glutamatergic Neuronal Excitability Are Involved in Prolonged Cognitive Dysfunction of Neonatal Rats Exposed to Propofol - Lin-Hui Ma; Jie Wan; Jing Yan; Ning Wang; Yan-Ping Liu; Hai-Bi Wang; Cheng-Hua Zhou; Yu-Qing Wu (Molecular Neurobiology, 2022)

Migration and abiotic transformation of estrone (E1) and estrone-3-sulfate (E1-3S) during soil column transport - Banghao Du; Weiwei Yu; Lun Yang; Gongduan Fan; Shuo Yang; Hui Jiang; Shenglan Bi; Cheng Yu (Environmental Geochemistry and Health, 2022)

Ero1‐Pdi1 module‐catalysed dimerization of a nucleotide sugar transporter, FonNst2 , regulates virulence of Fusarium oxysporum on watermelon - Yizhou Gao; Xiaohui Xiong; Hui Wang; Jiajing Wang; Yan Bi; Yuqing Yan; Zhongye Cao; Dayong Li; Fengming Song (Environmental Microbiology, 2022)
Summary Fusarium oxysporum f. sp. niveum ( Fon ) is a soil‐borne fungus causing vascular Fusarium wilt on watermelon; however, the molecular network regulating Fon virulence remains to be elucidated. Here, we report the function and mechanism of nucleotide sugar transporters (Nsts) in Fon . Fon genome harbours nine FonNst genes with distinct functions in vegetative growth, asexual production, cell wall stress response and virulence. FonNst2 and FonNst3 are required for full virulence of Fon on watermelon and FonNst2 is mainly involved in fungal colonization of the plant tissues. FonNst2 and FonNst3 form homo‐ or hetero‐dimers but function independently in Fon virulence. FonNst2, which has UDP‐galactose transporter activity in yeast, interacts with FonEro1 and FonPdi1, both of which are required for full virulence of Fon . FonNst2, FonPdi1 and FonEro1 target to endoplasmic reticulum (ER) and are essential for ER homeostasis and function. FonEro1‐FonPdi1 module catalyses the dimerization of FonNst2, which is critical for Fon virulence. Undimerized FonNst2 is unstable and degraded via ER‐associated protein degradation in vivo . These data demonstrate that FonEro1‐FonPdi1 module‐catalysed dimerization of FonNst2 is critical for Fon virulence on watermelon and provide new insights into the regulation of virulence in plant fungal pathogens via disulfide bond formation of key pathogenicity factors.

Transition in tectonic regime from the Paleo-Asian Ocean to Paleo-Pacific Ocean: constraints from the Jurassic adakitic and I-type granites, and calc-alkaline diorites at the northern margin of the North China Craton - Yan Jing; Wen-Chun Ge; Yu Dong; Hao Yang; Zheng Ji; Jun-Hui Bi; Hong-Ying Zhou; De-He Xing (International Geology Review, 2022)

Discerning the Putative U and V Chromosomes of Saccharina japonica (Phaeophyta) by Cytogenetic Mapping of Sex-Linked Molecular Markers - Yu Du; Peng-Fei Liu; Zhi Li; Qian Zheng; Yan-Hui Bi; Zhi-Gang Zhou (Frontiers in Marine Science, 2022)
Saccharina japonica , an importantly industrial species in brown seaweeds, has a typical alternate life history of heteromorphic generations and UV sex determination system. But up to now, the sex chromosomes, U and V, in this kelp remain to be evidenced cytologically. In the present study, the female-linked (SJ-f_000170 and MSj68-58-2) and male-linked (SJ-13_001840 and MSj68-16-2) molecular markers developed on the basis of Ectocarpus sex-determining regions (SDRs) were selected after PCR amplification and Southern blotting analysis. Mono-color fluorescence in situ hybridization (FISH) to the kelp metaphase chromosomes with each of these confirmed sex-linked markers as a probe indicated that the hybridization signals were confined to either female or male gametophytes exclusively. The shape and size of hybridized chromosomes and the relative location of these sex-linked markers on them suggested that the marked chromosomes in a sex were the same, which was further confirmed by dual-color FISH observations. SJ-f_000170 and SJ-13_001840, corresponding to each sex, were therefore used to map the sporophyte metaphase chromosomes by dual-color FISH technique, and they were hybridized on different chromosomes as expected. The sporophyte metaphase chromosomes as hybridized by SJ-f_000170 and SJ-13_001840 resembled those in either female or male gametophytes, suggesting that they were the putative U and V, respectively, chromosomes in S . japonica . To further demonstrate the reliability of this inference, genomic information of the screened bacterial artificial chromosome (BAC) clones carrying two female-linked markers, for example, from the constructed BAC libraries of the kelp female gametophytes was provided. The insert sequencing of two selected BAC clones revealed that repetitive elements were rich whereas gene density was poor, which was characterized as non-recombining SDR sequences in brown seaweed Ectocarpus sp. and liverwort Marchantia polymorpha . The present study laid a solid foundation for unveiling the mystery of S . japonica sex chromosomes.

Selenium Attenuates S. aureus-Induced Inflammation by Regulation TLR2 Signaling Pathway and NLRP3 Inflammasome in RAW 264.7 Macrophages - Ming-Ji Wei; Zhen-Nan Wang; Yan Yang; Shu-Jiu Zhang; He Tang; Hui Li; Chong-Liang Bi (Biological Trace Element Research, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

BLE-based floor positioning method for multi-level atrium spatial environments - Hongxia Qi; Yunjia Wang; Jingxue Bi; Hongji Cao; Shenglei Xu; Hui Liu (Acta Geodaetica et Geophysica, 2021)

Associations of Sleep Characteristics with Cerebrospinal Fluid sTREM2 in Cognitively Normal Older Adults: the CABLE Study - He-Ying Hu; Ling-Zhi Ma; Hao Hu; Yan-Lin Bi; Ya-Hui Ma; Xue-Ning Shen; Ya-Nan Ou; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Genipin Attenuates Tau Phosphorylation and Aβ Levels in Cellular Models of Alzheimer’s Disease - Meiting Li; Nan Cai; Liang Gu; Lijun Yao; Decheng Bi; Weishan Fang; Zhijian Lin; Yan Wu; Hong Xu; Hui Li; Zhangli Hu; Xu Xu (Molecular Neurobiology, 2021)

Genetic Analysis of ZNF Protein Family Members for Early-Onset Parkinson’s Disease in Chinese Population - Chun Yu Li; Ru Wei Ou; Yong Ping Chen; Xiao Jing Gu; Qian Qian Wei; Bei Cao; Ling Yu Zhang; Yan Bing Hou; Kun Cheng Liu; Xue Ping Chen; Wei Song; Bi Zhao; et al. (Molecular Neurobiology, 2021)

Exploring the influence of contributing factors and impact degree on bus emissions in real-world conditions - Chao Wang; Zhirui Ye; Hui Bi (Environmental Science and Pollution Research, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

A rapid and accurate method for identifying sexuality of Indarbela obliquifasciata Mell (Lepidoptera, Metarbelidae) adults and pupae - Li-Zhi Huo; Long-Hua Sun; Jing-Ai Zhang; Chao Wu; Ya-Hui Hou; Yong-Yue Wang; Zhi-Jie Li; Jia-Ru Deng; Si-Meng Yang; Ke-Ke Bi (International Journal of Tropical Insect Science, 2021)

Investigating the spatial distribution of polychlorinated biphenyls in sediment in the Pearl River Delta, South China - Man-Ying Chen; Hong-Yin Liu; Xiao-Jun Luo; Bi-Xian Mai; Feng-Hui Lu (Environmental Monitoring and Assessment, 2021)

Genetic Analysis of Prosaposin, the Lysosomal Storage Disorder Gene in Parkinson’s Disease - Yong-Ping Chen; Xiao-Jing Gu; Ru-Wei Ou; Ling-Yu Zhang; Yan-Bing Hou; Kun-Cheng Liu; Bei Cao; Qian-Qian Wei; Wei Song; Bi Zhao; Ying Wu; Jing-Qiu Cheng; et al. (Molecular Neurobiology, 2021)

Detection and significance of exosomal mRNA expression profiles in the cerebrospinal fluid of patients with meningeal carcinomatosis - Peng Cheng; Feifei Feng; Hui Yang; Suqin Jin; Chao Lai; Yun Wang; Jianzhong Bi (Journal of Molecular Neuroscience, 2021)

Short Communication: Effects of Dietary Selenium Supplementation on Selenium Deposition and Antioxidant Status in Postpartum Mice - Zhen-Nan Wang; Hui Li; He Tang; Shu-Jiu Zhang; Mirielle Pauline; Chong-Liang Bi (Biological Trace Element Research, 2021)

Middle–late permian I-type granitoids from the Diaobingshan region in the northern margin of the North China Craton: insight into southward subduction of the Paleo–Asian Ocean - Yan Jing; Zheng Ji; Wen-Chun Ge; Yu Dong; Hao Yang; Jun-Hui Bi (International Geology Review, 2021)

Modeling of Suffusion Considering the Influence of Soil Gradation - Jinfeng Bi; Xianqi Luo; Hui Shen (Transport in Porous Media, 2021)

The Salicylic Acid Signaling Pathway Plays an Important Role in the Resistant Process of Brassica rapa L. ssp. pekinensis to Plasmodiophora brassicae Woronin - Ruiqin Ji; Shiqi Gao; Qing Bi; Yilian Wang; Mingcan Lv; Wenjie Ge; Hui Feng (Journal of Plant Growth Regulation, 2021)

Selenium Plays an Anti-Inflammatory Role by Regulation NLRP3 Inflammasome in Staphylococcus aureus-Infected Mouse Mammary Gland - Chong-Liang Bi; Shu-Jiu Zhang; Yi-Zhao Shen; Mirielle Pauline; Hui Li; He Tang (Biological Trace Element Research, 2021)

Understanding the dynamical-microphysical-electrical processes associated with severe thunderstorms over the Beijing metropolitan region - Xiushu Qie; Shanfeng Yuan; Zhixiong Chen; Dongfang Wang; Dongxia Liu; Mengyu Sun; Zhuling Sun; Abhay Srivastava; Hongbo Zhang; Jingyu Lu; Hui Xiao; Yongheng Bi; et al. (Science China Earth Sciences, 2021)

Patterns of mitochondrial DNA fragmentation in bread wheat (Triticum aestivum L.) seeds under ex situ genebank storage and artificial aging - Yong-Bi Fu; Zaheer Ahmed; Hui Yang; Carolee Horbach; Gregory W. Peterson (Genetic Resources and Crop Evolution, 2020)

Immunocytochemical Localization of the Kinetochore Protein Nuf2p on the Gametophyte Chromosomes of a Cultivar of Saccharina (Phaeophyta) - Wu-Shan Dong; Peng-Fei Liu; Yu Liu; Yu Du; Yan-Hui Bi; Zhi-Gang Zhou (Frontiers in Marine Science, 2020)

Climate-Driven Range Shifts of Brown Seaweed Sargassum horneri in the Northwest Pacific - Jing-Jing Li; Sheng-Hui Huang; Zheng-Yi Liu; Yuan-Xin Bi (Frontiers in Marine Science, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Wild or farmed? A pilot study on determining origin of wildlife meat using methylation rate of ACTN3 gene and American mink - Bi Xiao Wang; Yue Ma; Yan Hua; Yan Chun Xu; Shu Hui Yang (Mammal Research, 2020)

Numerical Study on Hydrodynamic Responses of Floating Rope Enclosure in Waves and Currents - Hui Yang; Yun-Peng Zhao; Chun-Wei Bi; Yong Cui (Journal of Marine Science and Engineering, 2020)
Enclosure aquaculture is a healthy and ecological aquaculture pattern developed in recent years to relieve the pressure due to the wild fish stock decline and water pollution. The object of this paper was a floating rope enclosure, which mainly consisted of floaters, mooring lines, sinkers and a net. In order to optimize mooring design factors, the hydrodynamic responses of the floating rope enclosure with different mooring systems in combined wave-current were investigated by experimental and numerical methods. Physical model experiments with a model scale of 1:50 were performed to investigate the hydrodynamic characteristics of a floating rope enclosure with 12 mooring lines. Based on the lumped mass method, the numerical model was established to investigate the effects of mooring design factors on the mooring line tension, force acting on the bottom, and the volume retention of the floating rope enclosure. Through the analysis of numerical and experimental results, it was found that the maximum mooring line tension of the floating rope enclosure occurs on both sides of the windward. Increasing the number of mooring lines on the windward side is helpful to reduce the maximum mooring line tension. Waves and current both have an influence on the mooring line tension; in contrast, currents have a more obvious effect on the mooring line tension than waves. However, the influence of the wave period on the maximum mooring line tension is small. The force endured by the bottom of the floating rope enclosure also changes periodically with the wave period. Yet, the maximum force endured by the bottom of floating rope enclosure occurred at the windward and leeward of the structure. The volume retention of the floating rope enclosure increased with the increasing amount of mooring lines.

Two new norneolignans from Callicarpa kwangtungensis - Hong-Yu Bi; Chun-Liang Xu; Hui-Zheng Fu; Zhi-Qiang Zhou; Rui-Jian Zhong; Mian Dai; Dong Wang (Natural Product Research, 2020)

Differential Transcriptomic and Metabolomic Responses in the Liver of Nile Tilapia (Oreochromis niloticus) Exposed to Acute Ammonia - Zong Xian Zhu; Dan Li Jiang; Bi Jun Li; Hui Qin; Zi Ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

QTL Mapping for Red Blotches in Malaysia Red Tilapia (Oreochromis spp.) - Bi Jun Li; Zong Xian Zhu; Xiao Hui Gu; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Experimental Study on the Hydrodynamic Characteristics of a Submersible Fish Cage at Various Depths in Waves - Shengcong Liu; Chunwei Bi; Hui Yang; Liuyi Huang; Zhenlin Liang; Yunpeng Zhao (Journal of Ocean University of China, 2019)

Two new noroleanane-type triterpenoid saponins from the stems of Stauntonia chinensis - Tong-Tong Feng; Hui-Zheng Fu; Yi-Sheng Yang; Zhi-Qiang Zhou; Mian Dai; Hong-Yu Bi; Dong Wang (Natural Product Research, 2019)

Rapid identification of a candidate nicosulfuron sensitivity gene (Nss) in maize (Zea mays L.) via combining bulked segregant analysis and RNA-seq - Xiaomin Liu; Bo Bi; Xian Xu; Binghua Li; Shengmin Tian; Jianping Wang; Hui Zhang; Guiqi Wang; Yujun Han; J. Scott McElroy (Theoretical and Applied Genetics, 2019)

Identifying a Long QTL Cluster Across chrLG18 Associated with Salt Tolerance in Tilapia Using GWAS and QTL-seq - Dan Li Jiang; Xiao Hui Gu; Bi Jun Li; Zong Xian Zhu; Hui Qin; Zi ning Meng; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2019)

Stability analysis of complex rock slopes reinforced with prestressed anchor cables and anti-shear cavities - Jinfeng Bi; Xianqi Luo; Haitao Zhang; Hui Shen (Bulletin of Engineering Geology and the Environment, 2019)

Sea surface wind speed and sea state retrievals from dual-frequency altimeter and its preliminary application in global view of wind-sea and swell distributions - Shuiqing Li; Hui Shen; Yijun Hou; Yijun He; Fan Bi (International Journal of Remote Sensing, 2018)

TMEM230 Mutations Are Rare in Han Chinese Patients with Autosomal Dominant Parkinson’s Disease - Qianqian Wei; Ruwei Ou; Qingqing Zhou; Yongping Chen; Bei Cao; Xiaojing Gu; Bi Zhao; Ying Wu; Wei Song; Hui-Fang Shang (Molecular Neurobiology, 2018)

Determining the Effect of the HNMT, STK39, and NMD3 Polymorphisms on the Incidence of Parkinson’s Disease, Amyotrophic Lateral Sclerosis, and Multiple System Atrophy in Chinese Populations - Yongping Chen; Bei Cao; Ruwei Ou; Qianqian Wei; Xueping Chen; Bi Zhao; Ying Wu; Wei Song; Hui-Fang Shang (Journal of Molecular Neuroscience, 2018)

Synthesis and anticonvulsant activity of some novel 7-(benzylamino) -1H-benzo[b][1,4]diazepine-2,4(3H, 5H)-dione derivatives - Yun-Peng Shao; Rong-Bi Han; Hui-Fan Wu; Feng-Yu Piao (Medicinal Chemistry Research, 2018)

Identifying a Major QTL Associated with Salinity Tolerance in Nile Tilapia Using QTL-Seq - Xiao Hui Gu; Dan Li Jiang; Yan Huang; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2018)

CASCIRE surveillance network and work on avian influenza viruses - Yuhai Bi; Weifeng Shi; Jianjun Chen; Quanjiao Chen; Zhenghai Ma; Gary Wong; Wenxia Tian; Renfu Yin; Guanghua Fu; Yongchun Yang; William J. Liu; Chuansong Quan; et al. (Science China Life Sciences, 2017)

Role of scale interactions in the abrupt change of tropical cyclone in autumn over the Western North Pacific - Pang-Chi Hsu; Ting-Hui Lee; Chih-Hua Tsou; Pao-Shin Chu; Yitian Qian; Mingyu Bi (Climate Dynamics, 2017)

Genome-Wide QTL Analysis Identified Significant Associations Between Hypoxia Tolerance and Mutations in the GPR132 and ABCG4 Genes in Nile Tilapia - Hong Lian Li; Xiao Hui Gu; Bi Jun Li; Chao Hao Chen; Hao Ran Lin; Jun Hong Xia (Marine Biotechnology, 2017)

Characterization and physical mapping of nuclear ribosomal RNA (rRNA) genes in the haploid gametophytes of Saccharina japonica (Phaeophyta) - Li Liu; Qi-Fan Yang; Wu-Shan Dong; Yan-Hui Bi; Zhi-Gang Zhou (Journal of Applied Phycology, 2017)

Antioxidant activity of alcohol aqueous extracts of Crypthecodinium cohnii and Schizochytrium sp. - Jin-hui Yu; Yu Wang; Jie Sun; Fei Bian; Gao Chen; Yan Zhang; Yu-ping Bi; Ying-jie Wu (Journal of Zhejiang University-SCIENCE B, 2017)

Kitamycin C, a new antimycin-type antibiotic from Streptomyces antibioticus strain 200-09 - Fan Wang; Shu-Na Fu; Yi-Xuan Bao; Yu Yang; Hui-Fang Shen; Bi-Run Lin; Guang-Xiong Zhou (Natural Product Research, 2017)

Anti-hepatocellular carcinoma activity of tormentic acid derived from suspension cells of Eriobotrya japonica (Thunb.) Lindl. - Hui-Hua Li; Ming-Hua Su; De-Heng Yao; Bi-Yu Zeng; Qiang Chang; Wei Wang; Jian Xu (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Organic Solvent-Tolerant Marine Microorganisms as Catalysts for Kinetic Resolution of Cyclic β-Hydroxy Ketones - Bi -Shuang Chen; Hui Liu; Fayene Zeferino Ribeiro de Souza; Lan Liu (Marine Biotechnology, 2017)

Mutation Screening of the CHCHD10 Gene in Chinese Patients with Amyotrophic Lateral Sclerosis - QingQing Zhou; YongPing Chen; QianQian Wei; Bei Cao; Ying Wu; Bi Zhao; RuWei Ou; Jing Yang; XuePing Chen; Shinji Hadano; Hui-Fang Shang (Molecular Neurobiology, 2017)

Erratum to: Reliable Rate Measurements for Active and Passive Hepatic Uptake Using Plated Human Hepatocytes - Yi-an Bi; Renato J. Scialis; Sarah Lazzaro; Sumathy Mathialagan; Emi Kimoto; Julie Keefer; Hui Zhang; Anna M. Vildhede; Chester Costales; A. David Rodrigues; Larry M. Tremaine; Manthena V. S. Varma (The AAPS Journal, 2017)

Reliable Rate Measurements for Active and Passive Hepatic Uptake Using Plated Human Hepatocytes - Yi-an Bi; Renato J. Scialis; Sarah Lazzaro; Sumathy Mathialagan; Emi Kimoto; Julie Keefer; Hui Zhang; Anna M. Vildhede; Chester Costales; A. David Rodrigues; Larry M. Tremaine; Manthena V. S. Varma (The AAPS Journal, 2017)

Continental‐level population differentiation and environmental adaptation in the mushroom S uillus brevipes - Sara Branco; Ke Bi; Hui‐Ling Liao; Pierre Gladieux; Hélène Badouin; Christopher E. Ellison; Nhu H. Nguyen; Rytas Vilgalys; Kabir G. Peay; John W. Taylor; Thomas D. Bruns (Molecular Ecology, 2017)
Recent advancements in sequencing technology allowed researchers to better address the patterns and mechanisms involved in microbial environmental adaptation at large spatial scales. Here we investigated the genomic basis of adaptation to climate at the continental scale in Suillus brevipes , an ectomycorrhizal fungus symbiotically associated with the roots of pine trees. We used genomic data from 55 individuals in seven locations across North America to perform genome scans to detect signatures of positive selection and assess whether temperature and precipitation were associated with genetic differentiation. We found that S. brevipes exhibited overall strong population differentiation, with potential admixture in Canadian populations. This species also displayed genomic signatures of positive selection as well as genomic sites significantly associated with distinct climatic regimes and abiotic environmental parameters. These genomic regions included genes involved in transmembrane transport of substances and helicase activity potentially involved in cold stress response. Our study sheds light on large‐scale environmental adaptation in fungi by identifying putative adaptive genes and providing a framework to further investigate the genetic basis of fungal adaptation.

Two new sesquiterpenoids produced by halophilic Nocardiopsis chromatogenes YIM 90109 - Ming-Wei Sun; Xiao-Mei Zhang; Hui-Li Bi; Wen-Jun Li; Chun-Hua Lu (Natural Product Research, 2017)

Oral bioaccessibility and human exposure assessment of cadmium and lead in market vegetables in the Pearl River Delta, South China - Ping Zhuang; Yingwen Li; Bi Zou; Feng Su; Chaosheng Zhang; Hui Mo; Zhian Li (Environmental Science and Pollution Research, 2016)

Copper partitioning between granitic silicate melt and coexisting aqueous fluid at 850 °C and 100 MPa - Shuilong Wang; Hui Li; Linbo Shang; Xianwu Bi; Xinsong Wang; Wenlin Fan (Acta Geochimica, 2016)

Genome-wide study refines the quantitative trait locus for number of ribs in a Large White × Minzhu intercross pig population and reveals a new candidate gene - Long-Chao Zhang; Jing-Wei Yue; Lei Pu; Li-Gang Wang; Xin Liu; Jing Liang; Hua Yan; Ke-Bin Zhao; Na Li; Hui-Bi Shi; Yue-Bo Zhang; Li-Xian Wang (Molecular Genetics and Genomics, 2016)

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

Neprilysin Confers Genetic Susceptibility to Alzheimer’s Disease in Han Chinese - Hui-Zhen Wang; Rui Bi; Deng-Feng Zhang; Guo-Dong Li; Xiao-Hong Ma; Yiru Fang; Tao Li; Chen Zhang; Yong-Gang Yao (Molecular Neurobiology, 2016)

Enhancement of sediment phosphorus release during a tunnel construction across an urban lake (Lake Donghu, China) - Siyang Wang; Hui Li; Jian Xiao; Yiyong Zhou; Chunlei Song; Yonghong Bi; Xiuyun Cao (Environmental Science and Pollution Research, 2016)

Aquatic bioaccumulation and trophic transfer of tetrabromobisphenol-A flame retardant introduced from a typical e-waste recycling site - Lin Tao; Jiang-Ping Wu; Hui Zhi; Ying Zhang; Zi-He Ren; Xiao-Jun Luo; Bi-Xian Mai (Environmental Science and Pollution Research, 2016)

Special HMW-GSs and their genes of Triticum turgidum subsp. dicoccoides accession D141 and the potential utilization in common wheat - Xiao-Hui Guo; Ji-Liang Hu; Bi-Hua Wu; Zhen-Zhen Wang; Dong Wang; Deng-Cai Liu; You-Liang Zheng (Genetic Resources and Crop Evolution, 2016)

Petrogenesis of Early Cretaceous volcanic rocks of the Manketouebo Formation in the Wuchagou region, central Great Xing’an Range, NE China, and tectonic implications: geochronological, geochemical, and Hf isotopic evidence - Zheng Ji; Wen-Chun Ge; Qing-Hai Wang; Hao Yang; Guo-Chun Zhao; Jun-Hui Bi; Yu Dong (International Geology Review, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Validating GWAS-Identified Risk Loci for Alzheimer’s Disease in Han Chinese Populations - Hui-Zhen Wang; Rui Bi; Qiu-Xiang Hu; Qun Xiang; Chen Zhang; Deng-Feng Zhang; Wen Zhang; Xiaohong Ma; Wanjun Guo; Wei Deng; Liansheng Zhao; Peiyan Ni; et al. (Molecular Neurobiology, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

RETRACTED ARTICLE: Relationship of Serum Heart-Type Fatty Acid-Binding Protein Levels and Cerebral Infarction: a Meta-analysis - Bao-Liang Sun; Ming-Feng Yang; Xiao-Yi Yang; Jing-Yi Sun; Da-Wei Li; Zong-Yong Zhang; Lei-Lei Mao; Cun-Dong Fan; Cheng-Bi Zheng; Hong-Li Gao; Feng-Ze Wang; Feng Zhang; et al. (Molecular Neurobiology, 2015)

Erratum to: Neurogenic differentiation from adipose-derived stem cells and application for autologous transplantation in spinal cord injury - Yong Zhao; Hui Jiang; Xin-wei Liu; Jian-Ting Chen; Liang-Bi Xiang; Da-Peng Zhou (Cell and Tissue Banking, 2015)

Retraction Note to: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2015)

Neurogenic differentiation from adipose-derived stem cells and application for autologous transplantation in spinal cord injury - Yong Zhao; Hui Jiang; Xin-wei Liu; Jian-Ting Chen; Liang-Bi Xiang; Da-Peng Zhou (Cell and Tissue Banking, 2015)

The Transcriptome Study of Subtype M2 Acute Myeloblastic Leukemia - A-yang Wu; Hui-cong Yang; Cong-meng Lin; Bi-de Wu; Qi-shui Qu; Yuan-hai Zheng; Hua Wei; Xu-qiao Mei; Zhen-hua Zeng; Xu-dong Ma (Cell Biochemistry and Biophysics, 2015)

Heterologous biosynthesis of costunolide in Escherichia coli and yield improvement - Hua Yin; Yi-bin Zhuang; E-e Li; Hui-ping Bi; Wei Zhou; Tao Liu (Biotechnology Letters, 2015)

Microarray analysis of long non-coding RNAs in COPD lung tissue - Hui Bi; Ji Zhou; Dandan Wu; Wei Gao; Lingling Li; Like Yu; Feng Liu; Mao Huang; Ian M. Adcock; Peter J. Barnes; Xin Yao (Inflammation Research, 2015)

Particulate matter mass and chemical component concentrations over four Chinese cities along the western Pacific coast - Hong Xu; Xiao-Hui Bi; Wei-Wei Zheng; Jian-Hui Wu; Yin-Chang Feng (Environmental Science and Pollution Research, 2015)

RETRACTED ARTICLE: Text mining and network analysis of molecular interaction in non-small cell lung cancer by using natural language processing - Jun Li; Lintao Bi; Yanxia Sun; Zhenxia Lu; Yumei Lin; Ou Bai; Hui Shao (Molecular Biology Reports, 2014)

Cassiterite LA-MC-ICP-MS U/Pb and muscovite 40Ar/39Ar dating of tin deposits in the Tengchong-Lianghe tin district, NW Yunnan, China - Xiao-Cui Chen; Rui-Zhong Hu; Xian-Wu Bi; Hui-Min Li; Jiang-Bo Lan; Cheng-Hai Zhao; Jing-Jing Zhu (Mineralium Deposita, 2014)

Synthesis and anticonvulsant evaluation of some new 1,3,4,5-tetrahydro-6-alkoxy-2H-1-benzazepin-2-one derivatives - Rong-Bi Han; Yun-Peng Shao; Hui-Fan Wu; Duo Zhang; Feng-Yu Piao (Medicinal Chemistry Research, 2014)

Sex identification and genetic variation of Saccharina (Phaeophyta) gametophytes as revealed by inter-simple sequence repeat (ISSR) markers - Jun-Gang Gu; Yu-Ping Sun; Yu Liu; Yan-Hui Bi; Zhi-Gang Zhou (Journal of Applied Phycology, 2014)

Enterocin T, a novel class IIa bacteriocin produced by Enterococcus sp. 812 - Yi-sheng Chen; Chi-rong Yu; Si-hua Ji; Min-shiuan Liou; Kun-hon Leong; Shwu-fen Pan; Hui-chung Wu; Yu-hsuan Lin; Bi Yu; Fujitoshi Yanagida (Archives of Microbiology, 2013)

Retrieving the antarctic sea-ice concentration based on AMSR-E 89 GHz data - Qinglong Yu; Hui Wang; Liying Wan; Haibo Bi (Acta Oceanologica Sinica, 2013)

Recent advances in the study of testicular nuclear receptor 4 - Xian-fan Ding; Shi-cheng Yu; Bi-de Chen; Shin-jen Lin; Chawnshang Chang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2013)

Heavy metals in urban ambient PM10 and soil background in eight cities around China - Qiong Wang; Xiao-Hui Bi; Jian-Hui Wu; Yu-Fen Zhang; Yin-Chang Feng (Environmental Monitoring and Assessment, 2013)

Aggravated inflammation and increased expression of cysteinyl leukotriene receptors in the brain after focal cerebral ischemia in AQP4-deficient mice - Wen-Zhen Shi; Chun-Zhen Zhao; Bing Zhao; Qiao-Juan Shi; Li-Hui Zhang; Yan-Fang Wang; San-Hua Fang; Yun-Bi Lu; Wei-Ping Zhang; Er-Qing Wei (Neuroscience Bulletin, 2012)

A new plastic surgical technique for adult congenital webbed penis - Yue-bing Chen; Xian-fan Ding; Chong Luo; Shi-cheng Yu; Yan-lan YU; Bi-de Chen; Zhi-gen Zhang; Gong-hui Li (Journal of Zhejiang University-SCIENCE B, 2012)

A molecular mechanism underlying ovarian dysfunction of polycystic ovary syndrome: hyperandrogenism induces epigenetic alterations in the granulosa cells - Fan Qu; Fang-Fang Wang; Rong Yin; Guo-Lian Ding; Mohamed El-prince; Qian Gao; Bi-Wei Shi; Hui-Hui Pan; Yi-Ting Huang; Min Jin; Peter C. K. Leung; Jian-Zhong Sheng; et al. (Journal of Molecular Medicine, 2012)

Permissible Value for Vanadium in Allitic Udic Ferrisols Based on Physiological Responses of Green Chinese Cabbage and Soil Microbes - Xi-yuan Xiao; Miao Yang; Zhao-hui Guo; Yue-ping Luo; Jun-ping Bi (Biological Trace Element Research, 2012)

Chemical composition of precipitation and its sources in Hangzhou, China - Hong Xu; Xiao-Hui Bi; Yin-Chang Feng; Feng-Mei Lin; Li Jiao; Sheng-Mao Hong; Wen-Gao Liu; Xiao-Yong Zhang (Environmental Monitoring and Assessment, 2011)

Heavy Metals in Hair of Residents in an E-Waste Recycling Area, South China: Contents and Assessment of Bodily State - Jing Zheng; Xiao-Jun Luo; Jian-Gang Yuan; Luo-Yiyi He; Yi-Hui Zhou; Yong Luo; She-Jun Chen; Bi-Xian Mai; Zhong-Yi Yang (Archives of Environmental Contamination and Toxicology, 2011)

The Influence of Landscape Features on Road Development in a Loess Region, China - Xiaoli Bi; Hui Wang; Rui Zhou (Environmental Management, 2011)

Lack of association between methylenetetrahydrofolate reductase gene A1298C polymorphism and breast cancer susceptibility - Li-Xin Qiu; Jian Zhang; Wen-Hua Li; Qun-Ling Zhang; Hui Yu; Bi-Yun Wang; Lei-Ping Wang; Jia-Lei Wang; Hui-Jie Wang; Xiao-Jian Liu; Zhi-Guo Luo; Xiang-Hua Wu (Molecular Biology Reports, 2011)

Large-scale analysis of phosphorylated proteins in maize leaf - Ying-Dong Bi; Hong-Xia Wang; Tian-Cong Lu; Xiao-hui Li; Zhuo Shen; Yi-Bo Chen; Bai-Chen Wang (Planta, 2011)

The changes of densities and patterns of roads and rural buildings: a case study on Dongzhi Yuan of the Loess Plateau, China - Xiaoli Bi; Hui Wang; Jianping Ge (Environmental Monitoring and Assessment, 2010)

FAK is involved in invasion and metastasis of hepatocellular carcinoma - Jing-Song Chen; Xiao-Hui Huang; Qian Wang; Xi-Lin Chen; Xin-Hui Fu; Hao-Xiang Tan; Long-Juan Zhang; Wen Li; Jiong Bi (Clinical & Experimental Metastasis, 2010)

Transcriptional responses of Haemophilus parasuis to iron-restriction stress in vitro - Qiyun Xie; Hui Jin; Rui Luo; Yun Wan; Jie Chu; Hufeng Zhou; Bi Shi; Huanchun Chen; Rui Zhou (BioMetals, 2009)

Establishment and characterization of a new highly metastatic human osteosarcoma cell line - Yuxi Su; Xiaoji Luo; Bai-Cheng He; Yi Wang; Liang Chen; Guo-Wei Zuo; Bo Liu; Yang Bi; Jiayi Huang; Gao-Hui Zhu; Yun He; Quan Kang; et al. (Clinical & Experimental Metastasis, 2009)

Partial characterization of a hydrophobin protein Po.HYD1 purified from the oyster mushroom Pleurotus ostreatus - Ai Min Ma; Lin Jun Shan; Hui Jie Wang; Zhao Ping Du; Bi Jun Xie (World Journal of Microbiology and Biotechnology, 2008)

Hydrogen peroxide-induced chlorophyll a bleaching in the cytochrome b 6 f complex: a simple and effective assay for stability of the complex in detergent solutions - Xiao-Bo Chen; Xiao-Hui Zhao; Yi Zhu; Yan-Dao Gong; Liang-Bi Li; Jian-Ping Zhang; Ting-Yun Kuang (Photosynthesis Research, 2007)

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)

Improved paclitaxel production by in situ extraction and elicitation in cell suspension cultures of Taxus chinensis - Chang-He Zhang; Hui-Bi Xu (Biotechnology Letters, 2001)

Alteration of N-acetylglucosaminyltransferases in pancreatic carcinoma - Bi-cheng Nan; Dong-min Shao; Hui-li Chen; Yong Huang; Jian-xin Gu; Yi-bin Zhang; Zhao-guang Wu (Glycoconjugate Journal, 1998)